2021
DOI: 10.1371/journal.pone.0252924
|View full text |Cite
|
Sign up to set email alerts
|

The drug development pipeline for glioblastoma—A cross sectional assessment of the FDA Orphan Drug Product designation database

Abstract: Background Glioblastoma (GBM) is the most common malignant brain tumour among adult patients and represents an almost universally fatal disease. Novel therapies for GBM are being developed under the orphan drug legislation and the knowledge on the molecular makeup of this disease has been increasing rapidly. However, the clinical outcomes in GBM patients with currently available therapies are still dismal. An insight into the current drug development pipeline for GBM is therefore of particular interest. Obje… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Limitations and directions for future research. As pointed out previously, this analysis has some limitations that have to be taken into account for the correct interpretation of the present findings 21,22,27,[35][36][37] . Guided by strategic and patent related considerations manufacturers may choose not to reveal the intent to develop a drug in a publicly visible way at an early stage which may have influenced the timeline to approval in Fig.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Limitations and directions for future research. As pointed out previously, this analysis has some limitations that have to be taken into account for the correct interpretation of the present findings 21,22,27,[35][36][37] . Guided by strategic and patent related considerations manufacturers may choose not to reveal the intent to develop a drug in a publicly visible way at an early stage which may have influenced the timeline to approval in Fig.…”
Section: Discussionmentioning
confidence: 77%
“…This analysis focusses intentionally on the FDA perspective 40 and did therefore not consider regulatory jurisdictions elsewhere. Because in general drug development for rare diseases is a global endeavour, we regard the findings of the present analysis generalizable within the context of the limitations described 21 . This report serves as a baseline for future progress.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Goligher et al [ 25 ] examined respiratory muscle morphology by serial diaphragmatic ultrasound, thereby, both decreasing and increasing thickness was linked to increased PMV risk [ 25 ] The authors suggested that decreasing thickness is associated with abnormally low inspiratory effort and subsequent tissue atrophy, while increasing thickness is associated with excessive effort, possibly related to strain-induced muscle injury [ 25 ]. Relevant risk factors for prolonged weaning were baseline Glasgow Coma Scales (GCS) [ 26 ], elevated PaCO 2 at the beginning of [ 27 ] and during the first SBT [ 28 ], as well as heart rate during the first SBT [ 28 ] Hsieh et al [ 29 ] studied 47 different risk factors for prolonged weaning using an artificial neural network. The 47 input features included subject age, gender, scoring systems, such as Acute Physiology and Chronic Health Evaluation II (APACHE-II), Therapeutic Intervention Scoring System (TISS) and GCS, comorbidities, etiology of intubation and respiratory failure, pre-extubation parameters, weaning methods and parameters, and pre-extubation data.…”
Section: Resultsmentioning
confidence: 99%
“…After the treatment, GBM always recurs and turns out to be fatal rapidly since the current therapies are generally not very efficient and could hardly increase patients' survival time [4]. In the past four decades, only four drugs were approved by the FDA for GBM clinical treatment while three of them including TMZ are alkylating agents [5], which lack pertinence of oncogene and individual disease specificity. Because of all the above, GBM remains to be one of the most difficult-to-treat cancer types and there is an immense unmet medical need to develop more effective target therapies for this fatal disease.…”
Section: Introductionmentioning
confidence: 99%